Molecular And Immunological Characteristics Of Vibrio Cholerae And Vibrio Alginolyticus - Neela, Vasanthakumari (2000)
Twenty isolates of Vibrio cholerae and four isolates of Vibrio alginolyticus used in this study were identified using the conventional biochemical tests. All of the isolates were screened for the zonula occludens toxin gene (zot) by the Polymerase Chain Reaction (PCR) technique. The 1083 bp fragment of the zot gene was successfully amplified in all the tested isolates. Asymmetry PCR was used as a preliminary detection method and later confirmed through the gene probe method to test for the presence of the zot gene. Consequently, the zot gene was successfully cloned in pCR 2.1 TOPO vector and sequenced, in which the sequences were 99% homologous to the gene bank sequences.